2014
DOI: 10.1021/jo500981r
|View full text |Cite
|
Sign up to set email alerts
|

[Silver(I)(Pyridine-Containing Ligand)] Complexes As Unusual Catalysts for A3-Coupling Reactions

Abstract: Two original macrocyclic silver(I)(pyridine-containing ligand) complexes [Ag(I)(Pc-L)] were synthesized and characterized. Their ability to catalyze the coupling among aldehydes, terminal alkynes and amines (A(3)-coupling) was demonstrated. The reaction could be performed under conventional as well as dielectric heating. The catalysts were effective in both cases, but dielectric heating allowed a lower catalyst loading and reduced ratio among reaction partners in shorter reaction times. The reaction scope was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 80 publications
2
44
1
Order By: Relevance
“…Silver complexes 2 were easily obtained as white crystals in yields up to 91 % by precipitation, concentrating the solvent, and adding nhexane. Complexes 2a 1-3 and 2c 1,2 have been already described, [17,18] and experimental details for all others complexes can be found in the Experimental Section and in the Supporting Information. All the obtained silver complexes 2 have been fully characterized by 1 H and 13 C NMR spectroscopy, ESI-MS, and IR and UV/Vis spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Silver complexes 2 were easily obtained as white crystals in yields up to 91 % by precipitation, concentrating the solvent, and adding nhexane. Complexes 2a 1-3 and 2c 1,2 have been already described, [17,18] and experimental details for all others complexes can be found in the Experimental Section and in the Supporting Information. All the obtained silver complexes 2 have been fully characterized by 1 H and 13 C NMR spectroscopy, ESI-MS, and IR and UV/Vis spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the catalytic applications we previously reported for these compounds, [17,18] the interactions with alkynes are those of greatest interest. We found that 2c 1 reacted with a terminal alkyne, such as phenylacetylene, to give silver phenylacetylide 4 and the protonated ligand 3, which partially precipitated as the tetrafluoroborate salt.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations